High levels of TFAM repress mammalian mitochondrial DNA transcription in vivo - Bonekamp, Nina A.; Jiang, Min; Motori, Elisa; Villegas, Rodolfo Garcia; Koolmeister, Camilla; Atanassov, Ilian; Mesaros, Andrea; Park, Chan Bae; Larsson, Nils-Göran (Life science alliance, 2021)
Mitochondrial transcription factor A (TFAM) is compacting mitochondrial DNA (dmtDNA) into nucleoids and directly controls mtDNA copy number. Here, we show that the TFAM-to-mtDNA ratio is critical for maintaining normal mtDNA expression in different mouse tissues. Moderately increased TFAM protein levels increase mtDNA copy number but a normal TFAM-to-mtDNA ratio is maintained resulting in unaltered mtDNA expression and normal whole animal metabolism. Mice ubiquitously expressing very high TFAM levels develop pathology leading to deficient oxidative phosphorylation (OXPHOS) and early postnatal lethality. The TFAM-to-mtDNA ratio varies widely between tissues in these mice and is very high in skeletal muscle leading to strong repression of mtDNA expression and OXPHOS deficiency. In the heart, increased mtDNA copy number results in a near normal TFAM-to-mtDNA ratio and maintained OXPHOS capacity. In liver, induction of LONP1 protease and mitochondrial RNA polymerase expression counteracts the silencing effect of high TFAM levels. TFAM thus acts as a general repressor of mtDNA expression and this effect can be counterbalanced by tissue-specific expression of regulatory factors.